Habilidades blandas en estudiantes del quinto grado de secundaria en Instituciones Educativas del Distrito de Iquitos 2021 - Piña Gonzales, Annie Ruth (2024)
The objective of this study was to compare fifth year students’ soft skills in high schools in the district of Iquitos 2021 in terms of sex. Therefore, the type of research was comparative with field study, contemporary transectional and univariate designs. Likewise, the population was made up by 1858 and a sample of 263: 123 female and 140 male students. The data gathering tool used was a valid and reliable questionnaire. Results show that the mean score of male students is slightly above the mean score of female students in soft skills (75.683 > 75.663), which is in the range of "Adequate" category. The same happens in its dimensions: Assertive communication (75,146 < 75,267), collaboration (75,689 < 75,749), creativity (75,816 ˃ 75,668) and critical thinking (76,455 ˃ 76,445). In conclusion, there is no significant difference between female and male students’ soft skills, since the p-value was .907 > α = 0.05, rejecting the research hypothesis.